Integrating Islamic Legal Literacy and SDGs through a Pentahelix Collaboration to Counter Loan Shark Practice - Pertiwi, Dian; Nabilah, Wardatun; Octavia, Nurul Aini; Rizal, Deri (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to improve legal literacy among the community of Nagari Lima Kaum, Tanah Datar Regency, introduce alternative legal financing, and establish a healthy financial ecosystem through the Community Based Research approach and a collaborative Pentahelix strategy. The main activities include legal education, socialization of lawful financial transactions, cooperation with formal financial institutions, and empowerment of local leaders. The results indicate an increased understanding of the legal risks related to illegal loans, strengthened anti-loan shark attitudes, and improved community access to legal financing institutions. Synergistic collaboration among academics, government, community members, financial institutions, and media effectively reduces community dependence on loan sharks and promotes innovations in community-based and sharia-compliant financial services. Moreover, the program emphasizes continuous legal and financial education, the development of innovative and accessible financing services, and the strengthening of cross-sectoral synergies. These efforts collectively support inclusive, sustainable, and equitable local economic empowerment, fostering greater financial independence and resilience within the community.